Chondroitin sulphation patterns in synovial fluid in osteoarthritis subsets. Issue 7 (1st July 1999) - Lewis, Samantha; Crossman, Margot; Flannelly, Joanne; Belcher, Carolyn; Doherty, Michael; Bayliss, Michael T; Mason, Roger M
Abstract : OBJECTIVES: To determine concentrations of chondroitin sulphate (CS) disaccharides in knee synovial fluid (SF) from normal subjects and patients with osteoarthritis (OA) or rheumatoid arthritis (RA), to test whether these variables differ between different diseases and subsets of OA. METHODS: OA was subdivided into large joint OA (LJOA), nodal generalised OA (NGOA), and OA with calcium pyrophosphate crystal deposition (CPA), with 25, 9, and 11 people in each subset respectively. The SF of 13 normal subjects was also volunteered for analysis along with 15 RA patients. Clinical assessment of inflammation (0–6) was undertaken on OA and RA knees. Concentrations of unsaturated CS disaccharides Δdi6S and Δdi4S were measured by capillary zone electrophoresis. RESULTS: Concentrations of Δdi6S were lower in RA (5.90 ng/ml) and OA (13.24 ng/ml) fluids compared with normal (21.0 ng/ml) but no significant differences were seen between disease and normal fluids for Δdi4S (about 4–6 ng/ml). The ratio of Δdi6S:Δdi4S were RA<OA<normal subjects (p<0.001 for all comparisons). The disaccharide concentration values along with the ratios are below. Higher Δdi6S:Δdi4S ratios were obtained for LJOA and CPA compared with NGOA. Uninflamed knees had lower concentrations of Δdi6S than inflamed knees (p<0.01). In patients with bilateral samples, there were strong correlations between right and left knees for all SF variables. CONCLUSIONS: Altered ratios of CS sulphation patterns occur in OA and within OA subsets. These further justify considering NGOA as a subset with a different aetiopathogenesis.